Manajemen Pembelajaran Latihan Tabligh Untuk Menumbuhkan Mental Percaya Diri Santri - Aep Hidayat; Sofyan Sauri; Marwan Setiawan (Peneliti.net, 2022)
The background of the problem shows that some students have not been able to demonstrate proficiency in the practice of tabligh which has an effect on the unrealized achievement, namely growing mentally tough students. This study aims to determine and analyze the planning, implementation, evaluation of kyai's learning through tabligh training to cultivate tough santri mentality. The results of the study found that the learning of tabligh exercises to foster students' mental self-confidence was in accordance with the learning management function which included planning, implementation, evaluation and the components involved in it, obstacles/obstacles in learning tabligh exercises to foster students' mental self-confidence. namely the leadership figure factor as the main figure, the incompetent ustadz mentor in his field and infrastructure. The solution to minimize these obstacles was carried out on the leader's figure, namely scheduling the leader to always witness tabligh activities as student motivation, while the competence of the mentor teacher was carried out on an ongoing basis, and infrastructure facilities were gradually fulfilled as needed.